2023
DOI: 10.1002/ece3.10278
|View full text |Cite
|
Sign up to set email alerts
|

Genomic population structure and inbreeding history of Lake Superior caribou

Abstract: Caribou (Rangifer tarandus) have experienced dramatic declines in both range and population size across Canada over the past century. Boreal caribou (R. t. caribou), 1 of the 12 Designatable Units, has lost approximately half of its historic range in the last 150 years, particularly along the southern edge of its distribution. Despite this overall northward contraction, some populations have persisted at the trailing range edge, over 150 km south of the continuous boreal caribou range in Ontario, along the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…The genetic erosion captured in the southern range boundaries, particularly in Alberta and the Lake Superior coastal population in Ontario, was further highlighted by lower node-based metric values (closeness centrality and MIW) which could again be indicative of increased fragmentation and isolation of caribou in those regions. These results align with recent genomic studies focusing on runs of homozygosity which found evidence of increased inbreeding in Ontario’s coastal populations (Solmundson et al 2023). The reduced levels of genetic diversity (and hence the associated reduced adaptive potential) in the southern range extent has important management implications for boreal caribou, particularly since some areas showing low genetic diversity are within LPUs (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The genetic erosion captured in the southern range boundaries, particularly in Alberta and the Lake Superior coastal population in Ontario, was further highlighted by lower node-based metric values (closeness centrality and MIW) which could again be indicative of increased fragmentation and isolation of caribou in those regions. These results align with recent genomic studies focusing on runs of homozygosity which found evidence of increased inbreeding in Ontario’s coastal populations (Solmundson et al 2023). The reduced levels of genetic diversity (and hence the associated reduced adaptive potential) in the southern range extent has important management implications for boreal caribou, particularly since some areas showing low genetic diversity are within LPUs (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…The eastern portion of the range presented overall lower genetic diversity compared to the western portion of the range. The higher baseline genetic diversity in the west could be due to animals in the Northwest Territories being of Beringian-Eurasian Lineage (BEL) origin (Polfus et al 2017), in conjunction with overall higher levels of introgression into the North American Lineages (NAL) in the west – considering that genetic diversity and historical effective population sizes in the Beringian refugia during the Pleistocene were larger (Klütsch et al 2016; Taylor et al 2021; Solmundson et al 2023). By incorporating the first hierarchical community detection partition from the CIP network, we were able to control for the overall variation of genetic diversity between the eastern and western portions of the range and create interpolated raster surfaces that revealed genetic erosion occurring along the southern range periphery in both the east and west.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation